Steers Grazing a Rye Cover Crop Influence Growth of Rye and No‐Till Cotton. (1st November 2013) - Li, Yue; Allen, V. G.; Hou, F.; Chen, J.; Brown, C. P.
Abstract : Small grain cover crops offer grazing opportunities but effects on following row crops are not well understood. From 1999 through 2008, stocker steers ( Bos taurus ) grazed small grains in a two‐paddock crop rotation of rye ( Secale cereale L.), cotton ( Gossypium hirsutum L.), wheat ( Triticum aestivum L.), fallow, and rye. Treatments in 2005, 2007, and 2008 included (i) zero‐grazed rye from 1999; (ii) ungrazed rye in the current year only; (iii) always grazed rye; and (iv) in 2007 and 2008, monoculture cotton (since 1999) with no cover crop. The experiment, on a Pullman clay loam (fine, mixed, superactive, thermic Torrertic Paleustolls), was a randomized complete block design with three blocks. Ungrazed rye was mechanically harvested before planting cotton. Rye excluded from grazing in 1 yr only (Treatment 2) was taller ( P < 0.05) and produced more forage mass than zero‐grazed rye (Treatment 1), likely due to higher rye tiller numbers, weight, and basal cover. Cotton planted into grazed rye had more plants m –1 row and was taller until July ( P < 0.05), and in 2005 had greater ( P < 0.05) lint and seed yield than where grazing was excluded. Continuous cotton with no cover crop (Treatment 4) was shorter ( P < 0.01) than cotton grown with a cover crop regardless of grazing. Known allelopathic chemicals were detected in rye and soil where rye grew and appeared to be influenced by grazing. Increased growth and productivity of rye and cotton where grazing occurred may be related to suppressive effects of grazing on allelopathy.